2023
DOI: 10.1177/10664807231163259
|View full text |Cite
|
Sign up to set email alerts
|

Military Spouse Mental Health Outcomes After Receiving Short-Term Counseling Services

Abstract: Research related to military spouses accessing community-based mental health care is limited. Evaluations identifying outcomes of anxiety, depressive symptoms, and resilience are scant. In this study, 71 military partners and spouses (age M = 39.79, SD = 11.32; 97.2% women) receiving counseling services at a nonprofit agency completed self-report measures of anxiety, depressive symptoms, and resilience pre–post a 6-week intervention. Less depressive symptoms predicted higher resilience at intake of services, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…There have been studies using a resilience assessment in nontreatment-seeking FFs/EMTs (Joyce et al, 2019; Shahan et al, 2022), treatment-seeking first responders (Ponder, Walters, et al, 2023; Ramey et al, 2016), and one investigating military spouses (Prosek et al, 2023). Joyce et al (2019) utilized the Connor–Davidson Resilience Scale (CD-RISC) and the Brief Resilience Scale (BRS) and found that those with high resilience at baseline predicted decreases in PTSD, depression, and alcohol use 6 months later.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There have been studies using a resilience assessment in nontreatment-seeking FFs/EMTs (Joyce et al, 2019; Shahan et al, 2022), treatment-seeking first responders (Ponder, Walters, et al, 2023; Ramey et al, 2016), and one investigating military spouses (Prosek et al, 2023). Joyce et al (2019) utilized the Connor–Davidson Resilience Scale (CD-RISC) and the Brief Resilience Scale (BRS) and found that those with high resilience at baseline predicted decreases in PTSD, depression, and alcohol use 6 months later.…”
mentioning
confidence: 99%
“…Joyce et al (2019) utilized the Connor–Davidson Resilience Scale (CD-RISC) and the Brief Resilience Scale (BRS) and found that those with high resilience at baseline predicted decreases in PTSD, depression, and alcohol use 6 months later. However, a six-session counseling intervention on trauma exposed military spouses did not produce statistical or clinically significant changes in resilience (Prosek et al, 2023).…”
mentioning
confidence: 99%